Preparation and Powder XRD Analysis of Tris(2,2’-bipyridine)nickel(II) Trifluoroacetate - Kristian Handoyo Sugiyarto; Isana Supiah Yosephine Louise; Shinta Setya Wilujeng (Indonesian Journal of Chemistry, 2020)
The complex containing Ni(II)-2,2’-bipyridin (bipy)-trifluoroacetate (TFA) was prepared by direct interaction of the corresponding precursors in an aqueous solution. AAS measurement for metal content, TGA-DTA analysis and electrical conductance suggest the ionic complex of [Ni(bipy)3](CF3COO)2·6H2O. The magnetic moment of 3.13–3.17 BM indicates the paramagnetism corresponding to two unpaired electrons which is clearly higher than that of the spin only value (2.87 BM), and commonly observed due to the spin-orbit coupling in Ni(II). UV-Vis spectral property revealed the first two main ligand field bands centered at about 14200 and 18650 cm–1, which are attributed to the spin-allowed transition, 3A2g→3T2g and 3A2g→3T1g(F), respectively. The expected third band at higher energy seems to appear as a shoulder at 26500 cm–1 (378 nm), as it is masked by a strong intensity of charge transfer band centered at 31050 cm–1. The infrared spectrum exhibits mode of vibrations of the functional groups of ligand and TFA. The powder diffractogram was refined by Le Bail method and found fit as monoclinic system of space group of P21/M, with figures of merit: Rp = 3.62, Rwp = 5.76, Rexp = 3.48, goodness of fitting (GOF) 2.745 and the derived Bragg R-Factor = 0.05.